Ageing: from inflammation to cancer - Leonardi, Giulia C. (Immun Ageing, 2018)
Ageing is the major risk factor for cancer development. Hallmark of the ageing process is represented by inflammaging, which is a chronic and systemic low-grade inflammatory process. Inflammation is also a hallmark of cancer and is widely recognized to influence all cancer stages from cell transformation to metastasis. Therefore, inflammaging may represent the biological phenomena able to couple ageing process with cancer development. Here we review the molecular and cellular pathway involved in age-related chronic inflammation along with its potential triggers and their connection with cancer development.